Strategy for the Development of Educators in Improving the Quality of Education at Madrasah Tsanawiyah Baitul Makmur Curup - Meri Susiyanti; Irwan Fathurrochman; Rahmat Iswanto (INTERNATIONAL JOURNAL OF EDUCATIONAL REVIEW, 2022)
In the midst of intense competition between educational institutions today, it is necessary to have a strategy for educational institutions to continue to exist and be of high quality. Every educational institution should have a strategy in efforts to develop educators, because this will have an impact on the quality of the institution. The facts obtained are that the strategies used in development efforts, especially educators, are still less than optimal, resulting in the low quality of an educational institution. This is certainly a concern for all of us, so it is necessary for us to find solutions to these problems. This research is a field research conducted at MadrSasah Tsanawiyah Baitul Makmur, Curup District, Rejang Lebong Regency. The approach used is a qualitative descriptive approach. Sources of data obtained through observation, interviews and documentation. The data is then tested for validity, then analyzed through the process of data reduction, data presentation and drawing conclusions. The results showed that the development of teaching staff at Madrasah Tsanawiyah Baitul Makmur Curup was in the good category, but this needs to be improved. The development of educators at Madrasah Tsanawiyah Baitul Makmur Curup is carried out in several steps, including developing programs/planning, determining needs, determining targets, determining programs, identifying program implementation, implementing programs and evaluating program implementation. Meanwhile, the method of developing educators at Madrasah Tsanawiyah Baitul Makmur Curup is on the job training, consisting of job rotation, training, guidance / counseling, job instructor training, demonstrations, and temporary assignments, while off the job training (Training outside of work), consisting of courses, education and training, workshops, seminars, Subject Teacher Consultations, and comparative studies. Thus, it is hoped that Madrasah Tsanawiyah Baitul Makmur can excel in all fields and be able to compete with other Islamic educational institutions.